2016
DOI: 10.1080/15592294.2016.1154246
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative genome-wide methylation analysis of high-grade non-muscle invasive bladder cancer

Abstract: High-grade non-muscle invasive bladder cancer (HG-NMIBC) is a clinically unpredictable disease with greater risks of recurrence and progression relative to their low-intermediate-grade counterparts. The molecular events, including those affecting the epigenome, that characterize this disease entity in the context of tumor development, recurrence, and progression, are incompletely understood. We therefore interrogated genome-wide DNA methylation using HumanMethylation450 BeadChip arrays in 21 primary HG-NMIBC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 79 publications
3
35
0
Order By: Relevance
“…Several methylation markers previously shown to be associated with grade in bladder cancer are CD99 , CDH13 , RARB , RASSF1A , SFRP5 , and TMEFF2 [33] , [34] , [35] , [36] . A number of other markers of BC grade have also been shown specifically in NMIBC including ACTL5B , ATP5G2 , BCL2 , BRCA1 , CIDEA , DAPK , FRZB , HOXB2 , ITPKB , IRX1 , KRT13 , MGMT , MLL3 , RASSF1A , RUNX3 , TERT , TET2 , TRPA1 , VAX2 , and VHL [37] , [38] , [39] , [40] , [41] , [42] , [43] . Of these markers, several have been implicated across multiple studies, including BRCA1 , CDH13 , RASSF1A , and TMEFF2 , whereas other novel markers have emerged from only single studies thus far [24] , [33] , [35] , [37] , [39] , [44] , [45] , [46] .…”
Section: Discussionmentioning
confidence: 99%
“…Several methylation markers previously shown to be associated with grade in bladder cancer are CD99 , CDH13 , RARB , RASSF1A , SFRP5 , and TMEFF2 [33] , [34] , [35] , [36] . A number of other markers of BC grade have also been shown specifically in NMIBC including ACTL5B , ATP5G2 , BCL2 , BRCA1 , CIDEA , DAPK , FRZB , HOXB2 , ITPKB , IRX1 , KRT13 , MGMT , MLL3 , RASSF1A , RUNX3 , TERT , TET2 , TRPA1 , VAX2 , and VHL [37] , [38] , [39] , [40] , [41] , [42] , [43] . Of these markers, several have been implicated across multiple studies, including BRCA1 , CDH13 , RASSF1A , and TMEFF2 , whereas other novel markers have emerged from only single studies thus far [24] , [33] , [35] , [37] , [39] , [44] , [45] , [46] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also showed that PON3 is hypermethylated in colorectal cancer [ 9 ] and chordomas [ 21 ]. Notably, the genome-wide DNA methylation analysis identified that several genes, including PON3, are aberrantly methylated in the high-grade non-muscle invasive bladder cancer [ 22 ]. These findings suggest that epigenetic modifications are usually associated with the development and/or progression of different type of tumors [ 13 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Crosstalk genes including H2AFZ (synonym of H2A.Z) were annotated in ADM-PanIN-PDAC. Histones are found to be associated with the cancer-predisposing in ammation or even trans-differentiation [31]. Histone H3 has the potential to be a biomarker for evaluating the severity of acute pancreatitis due to caerulein triggered extensive pancreatic acinar cell death in animal model [32].…”
Section: Discussionmentioning
confidence: 99%